2021
DOI: 10.24248/eahrj.v5i1.658
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for diabetes mellitus among tuberculosis patients in Moshi Municipal Council, Kilimanjaro Tanzania

Abstract: Background: Diabetes Mellitus (DM) is a worldwide public health problem and its prevalence has been rising rapidly in low and middle income countries (LMICs) including Tanzania. According to WHO report 2015, DM is ranked number six as a leading cause of death worldwide. Strong evidence suggests that DM may be associated with Tuberculosis (TB) and could affect TB treatment outcomes. Tanzania is among the 22 countries that have a high burden of TB and currently facing increased epidemic of DM. The increasing dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
(57 reference statements)
0
3
0
1
Order By: Relevance
“…Berdasarkan data didapatkan juga median usia subyek ialah 51 tahun, rerata usia 54,1 tahun, usia tertinggi yaitu 82 tahun dengan jumlah satu orang dan usia terendah ialah 36 tahun dengan jumlah satu orang (Tabel 3). Penelitian oleh Mabula et al 16 melaporkan bahwa angka kejadian TB paru dengan DM didominasi oleh usia di atas 40 tahun. Marcoa et al 17 mendapatkan bahwa usia rerata pengidap TB paru dengan DM ialah 49,2 tahun.…”
Section: Bahasanunclassified
“…Berdasarkan data didapatkan juga median usia subyek ialah 51 tahun, rerata usia 54,1 tahun, usia tertinggi yaitu 82 tahun dengan jumlah satu orang dan usia terendah ialah 36 tahun dengan jumlah satu orang (Tabel 3). Penelitian oleh Mabula et al 16 melaporkan bahwa angka kejadian TB paru dengan DM didominasi oleh usia di atas 40 tahun. Marcoa et al 17 mendapatkan bahwa usia rerata pengidap TB paru dengan DM ialah 49,2 tahun.…”
Section: Bahasanunclassified
“…The ADEPT implementation included three regions-Dar es Salaam, Iringa and Kilimanjaro. Prevalence of DM in the general population in Dar es Salaam and Kilimanjaro is 9% and 5.7%, while the prevalence of DM in people with TB is estimated at 9.7% and 9.2%, respectively [7,21,22]. Studies of the magnitude of DM in the general population in Iringa were lacking, but one study found a prevalence of DM among people with TB of approximately 9% [23].…”
Section: Contextmentioning
confidence: 99%
“…Among these studies, 79 (238,316 participants) were included in the meta-analysis for smoking, 67 (52,793 participants) for current alcohol use, 30 (31,450 participants) for hazardous alcohol use, 51 (37,879 participants) for DM, 19 (18,211 participants) for hypertension and 18 (13,910 participants) for obesity. Two studies (4320 participants) 29,30 reported on lipid abnormalities and another two studies 31,32 reported Prevalence of smoking. The pooled prevalence of any history of smoking was 26.0% (95% CI 22.0-29.0, I 2 = 99.6%, p < 0.001) and ranged from 1.4% in Uganda 33 to 82.5% in South Africa 34 .…”
Section: Study Characteristicsmentioning
confidence: 99%
“…of people with TB had low high density lipoproteins in Nigeria 29 while only 1.7% self-reported any lipid abnormalities in South Africa 30 . Physical inactivity, defined as a sedentary occupation and "no physical exercise", was reported in 49.8% of people with TB in Nigeria and 69.9% in Tanzania, respectively 31,32 . In the study from Nigeria, 32.9% had moderate activity and 17.3% had occupations associated with vigorous activity.…”
Section: Prevalence Of Lipid Abnormalities and Physical Inactivity Wi...mentioning
confidence: 99%